KOMPOSISI JENIS VEGETASI HUTAN PADA KESATUAN PENGELOLAAN HUTAN PRODUKSI (KPHP) SIVIA PATUJU KABUPATEN TOJO UNA-UNA PROVINSI SULAWESI TENGAH - Muzaki, Muhammad Shaffa; Mallombasang, Sri Ningsih; Sustri, Sustri (Universitas Tadulako, 2017)
Forest area in Indonesia divided into Forest Management Unity units(KPH) for the implementation of efficiency and preservation of forest management. Research about the composition of forest vegetation species of Forest Management Unity at Sivia Patuku was conducted as an additional basic information in managing the forest preservely at Production Forest Management Unity Sivia Patuju. The objective of the research was to find out the composition of forest vegetation species at PFMU Sivia Patuju, Tojo Una-Una district Central Sulawesi Province. The research was conducted on February to March 2015. The research location was at Production Forest Management Unity Sivia Patuju. The method applied in the research was done based on technical instruction of forest inventory on the area of Protected Forest Management Unity and Production Forest Management Unity of Forestry Ministry. Plot sampling on inventory of Production Forest Management Unity was a square form, with size 100 m x 100 m or 1 Ha large. Each plot consisted of 16 sub-plot, which each plot had size 25 m x 25 m. On each sub-plot measured by standing parameters and growing places. The result showed that dominant vegetation species on tree level was Nyatoh (Palaquium sp.) on function of production and protected forest at Production Forest Management Unity Sivia Patuju with each INP value 84,39 % and 67,57%, while on function of Limited Production Forest, the dominant spcies was Sengon (Paraserianthes falcataria (L) Nielsen) with IVI (INP) 55,87%. The research gave information that the dynamic of composition of forest vegetation at Production Forest Management Unity Sivia Patuju obviously happened. The rejuvenescence will affect forest dynamic in the future. The higher in number or density, distribution and areal expansion of vegetation regeneration species, the possibility to be a tree will be higher.Keywords : Composition, Vegetation, KPHP Sivia Patuju